Biomimetic Proteoglycans for Intervertebral Disc (IVD) Regeneration - Neha Chopra; James Melrose; Zi Gu; Ashish D. Diwan (Biomimetics)
Intervertebral disc degeneration, which leads to low back pain, is the most prevalent musculoskeletal condition worldwide, significantly impairing quality of life and imposing substantial socioeconomic burdens on affected individuals. A major impediment to the development of any prospective cell-driven recovery of functional properties in degenerate IVDs is the diminishing IVD cell numbers and viability with ageing which cannot sustain such a recovery process. However, if IVD proteoglycan levels, a major functional component, can be replenished through an orthobiological process which does not rely on cellular or nutritional input, then this may be an effective strategy for the re-attainment of IVD mechanical properties. Furthermore, biomimetic proteoglycans (PGs) represent an established polymer that strengthens osteoarthritis cartilage and improves its biomechanical properties, actively promoting biological repair processes. Biomimetic PGs have superior water imbibing properties compared to native aggrecan and are more resistant to proteolytic degradation, increasing their biological half-life in cartilaginous tissues. Methods have also now been developed to chemically edit the structure of biomimetic proteoglycans, allowing for the incorporation of bioactive peptide modules and equipping biomimetic proteoglycans as delivery vehicles for drugs and growth factors, further improving their biotherapeutic credentials. This article aims to provide a comprehensive overview of prospective orthobiological strategies that leverage engineered proteoglycans, paving the way for novel therapeutic interventions in IVD degeneration and ultimately enhancing patient outcomes.